Balance and fear of falling in subjects with Parkinson's disease is improved after exercises with motor complexity - Silva-Batista, Carla; Corcos, Daniel M.; Kanegusuku, Helcio; Pimentel Piemonte, Maria Elisa; Bucken Gobbi, Lilian Teresa [UNESP]; Lima-Pardini, Andrea C. de; Mello, Marco Tulio de; Forjaz, Claudia L. M.; Ugrinowitsch, Carlos (Elsevier B.V., 2018)
Resistance training with instability (RTI) uses exercises with high motor complexity that impose high postural control and cognitive demands that may be important for improving postural instability and fear of falling in subjects with Parkinson's disease (PD). Here, we hypothesized that: 1) RTI will be more effective than resistance training (RT) in improving balance (Balance Evaluation Systems Test [BESTest] and overall stability index [Biodex Balance System (R)]) and fear of falling (Falls Efficacy Scale-International [FES-I] score) of subjects with Parkinson's disease (PD); and 2) changes in BESTest and FES-I after RTI will be associated with changes in cognitive function (Montreal Cognitive Assessment [MoCA] score -previously published) induced by RTI. Thirty-nine subjects with moderate PD were randomly assigned to a nonexercising control, RT, and RTI groups. While RT and RTI groups performed progressive RT twice a week for 12 weeks, the RTI group added progressive unstable devices to increase motor complexity of the resistance exercises. There were significant group x time interactions for BESTest, overall stability index, and FES-I scores (P < 0.05). Only RTI improved BESTest, overall stability index and FES-I scores, and RTI was more effective than RT in improving biomechanical constraints and stability in gait (BESTest sections) at post-training (P < 0.05). There were strong correlations between relative changes in BESTest and MoCA (r= 0.72, P= 0.005), and FES-I and MoCA (r=-0.75, P= 0.003) after RTI. Due to the increased motor complexity in RTI, RTI is recommended for improving balance and fear of falling, which are associated with improvement in cognitive function of PD.
Keywords: Resistance training; Unstable device; Postural instability; Fall; Cognitive impairment; Muscle strength